2020
DOI: 10.1002/pssa.202000665
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Performance Enhancement of All‐Inorganic CsPbBr3 Perovskite Solar Cells Using In2S3 as Electron Transport Layer via Facile Reflux‐Condensation Process

Abstract: All‐inorganic perovskite solar cells (PSCs) have attracted tremendous attention over the past few years owing to their outstanding thermal and moiture stability. Electron transport layers (ETLs) in PSCs play a prominent role of electron extraction and transportation as well as hole blocking for a high power conversion efficiency (PCE). Indium sulfide (In2S3) films have been introduced as a promising ETL of PSCs recently due to their high carrier mobility, appropriate band gap, and controllable electrical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…All the In 2 S 3 films were spin coated at the optimal speed of 3000 rpm and subsequently annealed at 300 °C in Ar atmosphere for 1 h according to our previous work. [ 40 ] The surface morphologies of the In 2 S 3 films obtained by four different reflux condensation temperatures are basically the same, which seem like many particle aggregates (about 100–150 nm) composed of smaller grains (about 10 nm), as shown in Figure 2 . However, when the reflux condensation temperature is 80 °C, the particle size is obviously smaller than the other three samples; while the temperature is 100 and 120 °C, the particle size is almost the same, which is between those of 80 and 140 °C; the particle size becomes larger as the temperature continues increasing up to 140 °C.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…All the In 2 S 3 films were spin coated at the optimal speed of 3000 rpm and subsequently annealed at 300 °C in Ar atmosphere for 1 h according to our previous work. [ 40 ] The surface morphologies of the In 2 S 3 films obtained by four different reflux condensation temperatures are basically the same, which seem like many particle aggregates (about 100–150 nm) composed of smaller grains (about 10 nm), as shown in Figure 2 . However, when the reflux condensation temperature is 80 °C, the particle size is obviously smaller than the other three samples; while the temperature is 100 and 120 °C, the particle size is almost the same, which is between those of 80 and 140 °C; the particle size becomes larger as the temperature continues increasing up to 140 °C.…”
Section: Resultsmentioning
confidence: 78%
“…In our previous work, we have demonstrated that the electron extraction and transfer capability of the In 2 S 3 film from CsPbBr 3 perovskite film was superior to that of the TiO 2 film, compared with the FTO/CsPbBr 3 structure without In 2 S 3 or TiO 2 ETL. [ 40 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CsPbBr 3 perovskite exhibits the most excellent heat, moisture, and ultraviolet light resistance, showing great potential applications in semitransparent or top-cell of tandem solar cells with Cu(In, Ga)Se 2 or crystalline silicon solar cells. [9][10][11][12][13][14] In the past several years, many important works have been done to improve the photovoltaic performance of CsPbBr 3 PSCs. Kulbak et al first proposed CsPbBr 3 as light absorption material, and the fluorine-doped tin oxide (FTO)/c-TiO 2 /m-TiO 2 / CsPbBr 3 /hole transport layer (HTL)/Au structured solar cell produced the highest PCE of 5.95 %, with open circuit voltage (V oc ) of 1.28 V, short current density (J sc ) of 6.24 mA/cm 2 and fill factor (FF) of 74 %.…”
Section: Introductionmentioning
confidence: 99%
“…However, both CsPbI 3 and CsPbI 3‐x Br x perovskites easily transform into non‐perovskite phase in air atmosphere, which hinders their practical applications. The CsPbBr 3 perovskite exhibits the most excellent heat, moisture, and ultraviolet light resistance, showing great potential applications in semitransparent or top‐cell of tandem solar cells with Cu(In, Ga)Se 2 or crystalline silicon solar cells [9–14] …”
Section: Introductionmentioning
confidence: 99%